Leveraging Advanced Technologies to Enhance Learning Experiences in the Era 5.0 - I Gede Dharman Gunawan; I Wayan Sindia Griya Danika; Miko Miko (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2023)
Education is one of the sectors significantly influenced by technological advancements. In the era of 5.0, characterized by further integration of technology into everyday life, education faces new challenges and opportunities in creating better and more relevant learning experiences for the younger generation. Education plays a crucial role in shaping individuals, preparing them for the future, and building an advanced society. The rapid development of technology in the 5.0 era, marked by deeper integration of technology into daily life, presents new challenges and incredible opportunities for education. This study aims to explore the utilization of advanced technology in enhancing learning experiences in the 5.0 era. With a focus on artificial intelligence, virtual and augmented reality, intelligent tutoring systems, as well as the use of technology in assessment and feedback, this research illustrates the positive impact of advanced technology on student engagement, academic achievement, and skill development. Research findings indicate that successful implementation in educational environments has brought significant changes in students learning experiences. However, it is important to consider ethical considerations and responsible use of technology to ensure inclusive and sustainable adoption of advanced technology in education. Recommendations such as proper investment, teacher training and development, student-centered approaches, collaboration, ongoing evaluation, and partnerships with industries and the workforce serve as essential foundations in facing the future of education. Thus, this research provides valuable insights into the utilization of advanced technology in enhancing learning experiences and the future perspective of education.